Esensi otonomi Daerah Yang Ideal Menurut Sistem UUD NRI tahun 1945 - Yohanes Taryono; Juanda Juanda (SALAM: Jurnal Sosial dan Budaya Syar-i, 2021)
In realizing a prosperous region, the principles of decentralization, deconcentration and co-administration must be carried out simultaneously which is flowed in one pipe, the principle of regional autonomy. The research method used is normative juridical research with a statutory approach. Legal regulations are the focal point of the object and the main theme in this research. The research specification is descriptive analysis with the object of regional autonomy and the laws and regulations that underlie it. The results of the study stated that the essence of the ideal implementation of regional autonomy according to the 1945 Constitution of the Republic of Indonesia lies in the independence of the autonomous region in drafting Regional Regulations between the DPRD and the Regional Head. This is because the DPRD is directly elected by the local people in a democratic manner. DPRD as the representative of the regional people is a reflection of the aspirations of the regional people in realizing quality and aspirational regional regulations as a means of realizing independence, quality services and the welfare of the regional people.Keywords: Unitary State Principles; Regional autonomy; Local regulation AbstrakDalam mewujudkan daerah yang sejahtera, prinsip desentralisasi, dekonsentrasi dan tugas pembantuan harus dilaksanakan secara bersamaan yang dialirkan dalam satu pipa prinsip otonomi daerah. Metode penelitian yang digunakan yakni penelitian yuridis normatif dengan pendekatan perundang-undangan Peraturan hukum menjadi titik fokus objek dan tema utama dalam penelitian ini. Spesifikasi penelitian yakni dengan deskriptif analisis dengan objek otonomi daerah dan peraturan perundang-undangan yang melandasinya. Hasil penelitian menyatakan bahwa esensi pelaksanaan otonomi daerah yang ideal menurut UUD NRI 1945 terletak pada kemandirian daerah otonom dalam menyusun Peraturan Daerah antara DPRD bersama Kepala Daerah. Sebab DPRD dipilih langsung oleh rakyat daerah secara demokratis. DPRD sebagai wakil rakyat daerah merupakan cerminan aspirasi rakyat daerah dalam mewujudkan peraturan daerah yang berkualitas dan aspiratif sebagai sarana mewujudkan kemandirian, pelayanan yang bermutu dan kesejahteraan rakyat daerah.Kata Kunci: Prinsip Negara Kesatuan; Otonomi Daerah; Peraturan Daerah